BISAKAH AKU PAKAI INI KE HANGOUT? KETIKA SEPATU BASKET MELANGKAH KE DUNIA KASUAL - Muhamad Amar Ma’ruf; Agatha Dinarah Sri Rumestri; Laurensius Windy Octanio Haryanto (Telkom University, 2025)
High cut basketball shoes are known for their superiority in providingoptimal stability for the user's feet. However, this safety feature often sacrificesflexibility of movement, which is a challenge for athletes. This problem is increasinglyrelevant with the finding that teenage male basketball athletes use basketball shoesnot only for sports needs, but also as a means of expressing themselves in the socialsphere known as athleisure. This phenomenon gives rise to the concept of